Studi Hubungan Drilling Rate Index Dengan Uniaxial Compressive Strength Pada Batupasir Formasi Pulaubalang dan Formasi Kampungbaru - Nurul Idar Ilahi Bakti; Revia Oktaviani; Harjuni Hasan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Drilling capability, is one of the most important considerations in rock excavation, which can be defined as the ease of drilling a rock mass at a certain time for a long period of time with a drill bit. Rock drilling capabilities are influenced by various factors related to drilling machine working parameters and geotechnical characteristics of the rock mass (Yenice, 2019). Based on the above, this research was carried out to determine the UCS value in rock samples and the relationship formed by the DRI test value with the value produced in the UCS test using a regression analysis graph.